The follower’s ruling on the Almighty’s saying "O mountains of Ubi, with him and the birds": A semantic grammatical study - Zaidan , Shaimaa (Al-Adab Journal, 2025)
This study aims to explain the rulings on the caller’s subordinate, defined by the singular conjunction, which is the word (bird), after mentioning the types of subordinates in a brief and simplified manner, then explaining the rulings on its subordinate, especially the dependent, defined by the singular conjunction, then explaining the parsing of the word (bird) from the Almighty’s saying.} O mountains of Ubi with him and the birds {} Sheba / 10 {, and an explanation of the semantic impact of the multiplicity of readings and grammatical aspects in the interpretation of the Qur’anic text.This study was divided into an introduction and three axes, followed by a conclusion. It was supported by the sources and references of the study. The first was entitled (On the followers of Arabic and its types), and the second (Rulings on the caller’s follower, defined by the singular conjunction), and the third (The grammatical aspects of the caller’s follower, defined by the singular conjunction.  The fourth was entitled (The meanings of the nominative and accusative in guiding the interpretation of the word (bird)).